Geotechnical engineering properties of peat stabilized with a combination of fly ash and well graded sand. - Venuja, S.; Mathiluxsan, S.; Nasvi, M.C.M. (Engineer: Journal of the Institution of Engineers, Sri Lanka, 2017)
Peat has several unfavourable characteristics such as low bearing capacity, high compressibility, high content of natural water and difficulty of access and thus is not suitable for Civil Engineering constructions. One of the widely used techniques for its improvement is its chemical stabilization through the addition of chemical admixtures such as ordinary Portland cement, lime, fly ash, natural fillers etc. This research was focused on stabilizing peat using low Ca fly ash (ASTM Class F) combined with well graded sand. An experimentally based approach was followed to analyse the stabilization of peat samples with different proportions of fly ash (10, 20 and 30 % by weight) and 125 kg/m3 of well graded sand. With the increase in the fly ash content, the Maximum Dry Density (MDD) increased while the Optimum Moisture Content (OMC) decreased. The Unconfined Compressive Strength (UCS) increased with the addition of fly ash up to 10 % by weight and thereafter it began to reduce as more and more fly ash was added. The UCS increase with curing period for all of the stabilized samples. Rowe cell test results showed that there was an improvement in the compressibility of peat after stabilization. On the whole, it was found that the geotechnical engineering properties of peat can be improved by stabilizing it using fly ash and well graded sand.
Keywords: Chemical stabilization; Fly ash; Peat; Rowe cell; Unconfined compressive strength